Therapeutic role of voltage-gated potassium channels in age-related neurodegenerative diseases - Urrutia, Janire; Arrizabalaga-Iriondo, Ane; Sanchez-del-Rey, Ana; Martinez-Ibargüen, Agustín; Gallego, Mónica; Casis, Oscar; Revuelta, Miren (Frontiers in Cellular Neuroscience, 2024)
Voltage-gated ion channels are essential for membrane potential maintenance, homeostasis, electrical signal production and controlling the Ca 2+ flow through the membrane. Among all ion channels, the key regulators of neuronal excitability are the voltage-gated potassium channels (KV), the largest family of K + channels. Due to the ROS high levels in the aging brain, K + channels might be affected by oxidative agents and be key in aging and neurodegeneration processes. This review provides new insight about channelopathies in the most studied neurodegenerative disorders, such as Alzheimer Disease, Parkinson´s Disease, Huntington Disease or Spinocerebellar Ataxia. The main affected KV channels in these neurodegenerative diseases are the KV1, KV2.1, KV3, KV4 and KV7. Moreover, in order to prevent or repair the development of these neurodegenerative diseases, previous KV channel modulators have been proposed as therapeutic targets.